Convenção de Minamata: análise dos impactos socioambientais de uma solução a longo prazo - Silva, Rafaela Rodrigues da [UNIFESP] (2016)
This study aims to analyze the socio-environmental impacts of a long-term solution admitted in Minamata Convention, in order to bring some light on the potential environmental, social and economic consequences of the continued use of mercury - which is a toxic metal, liquid at room temperature and highly volatile even at zero degrees Celsius, - specifically in activities such as chlor-alkali and fluorescent lamps, also considering, besides the affected environmental compartments, fauna, flora and human segments such as vulnerable to mercury exposure, including in it the workers. There were used literature review, documentary research and use of images in order to better locate and measure the impacts of mercury. The Complexity Theory was used as theoretical base to the dissertation, which presents the Case Study of a chlor-alkali industry, as well as the analysis of fluorescent lamps through the DPSIR method. The research allowed to review the inherent hazard of the mercury and its compounds, that are an endocrine disruptor, and also revealed how much the society is still dependent on obsolete technologies, and the use of mercury is still not being properly controlled by government bodies. The conclusion is that, despite reliable estimates of metal air emissions and its environmental damage - which, by extension, affect from the biota to public health and collective, - obsolete production processes involving mercury, for various political reasons and lucrative economic interests, will remain for a long time. Considering only the chlor-alkali and lamps segments, only Brazil will emit, during the moratorium offered in the framework of Minamata Convention, about 18,700 tons of mercury. The Convention, despite that flexibility, is still in the long process of signature and ratification by countries, having currently 128 signatures and 28 ratifications, entering into force as International Law ninety days after the fiftieth country deposit of its instrument of ratification. In final conclusion, human beings have to break the spell with this phenomenon and face the objective and subjective complexity of the facts in order to to think and act in solidarity, because mankind has a common destiny on the planet, and self-reflection and self-analysis is one of the ways. As Morin indicates, there is the need of reforming the thinking.